Marine Radiocarbon Reservoir Values in Southern California Estuaries: Interspecies, Latitudinal, and Interannual Variability. Issue 3 (2015) - Holmquist, James R; Reynolds, Laura; Brown, Lauren N; Southon, John R; Simms, Alexander R; MacDonald, Glen M
Abstract : Many studies use radiocarbon dates on estuarine shell material to build age-depth models of sediment accumulation in estuaries in California, USA. Marine 14 C ages are typically older than dates from contemporaneous terrestrial carbon and local offsets (ΔR) from the global average marine offset need to be calculated to ensure the accuracy of calibrated dates. We used accelerator mass spectrometry (AMS) 14 C dating on 40 pre-1950 salt marsh snail and clam shells previously collected from four California estuaries. The average ΔR and standard deviation of 217 ± 129 14 C yr is consistent with previous calculations using mixed estuarine and marine samples, although the standard deviation and resulting age uncertainty was higher for our estuarine calculations than previous studies. There was a slight but significant difference ( p = 0.024) in ΔR between epifaunal snails (ΔR = 171 ± 154 14 C yr) and infaunal clams (ΔR = 263 ± 77 14 C yr), as well as between samples from individual estuaries. However, a closer examination of the data shows that even for the same species, at the same estuary, ΔR can vary as much as ∼500 14 C yr. In some cases, the bulk of this variation occurs between samples collected by different collectors at different times, potentially indicating time dependence in carbon sources and ΔR variation. These variations could also be attributed to differences in collection location within a single estuary and resulting spatial differences in carbon sources. Intertidal specimens located in the high marsh may have lower ΔR than fully marine counterparts because of increased terrestrial 14 C input. The large variations in ΔR here highlight the need for conservative chronological interpretations, as well as the assumption of wide uncertainties, when dating samples from estuarine sources.